Roles of HMGB1 in regulating myeloid-derived suppressor cells in the tumor microenvironment - Shuiling Jin (Biomarker Research, 2020)
Abstract Myeloid-derived suppressor cells (MDSCs) are notable contributors to the immunosuppressive tumor microenvironment (TME) and are closely associated with tumor progression; in addition, MDSCs are present in most patients with cancer. However, the molecular mechanisms that regulate MDSCs in the etiopathogenesis of human tumor immunity remain unclear. The secreted alarmin high mobility group box 1 (HMGB1) is a proinflammatory factor and inducer of many inflammatory molecules during MDSC development. In this review, we detail the currently reported characteristics of MDSCs in tumor immune escape and the regulatory role of secreted HMGB1 in MDSC differentiation, proliferation, activity and survival. Notably, different posttranslational modifications of HMGB1 may have various effects on MDSCs, and these effects need further identification. Moreover, exosome-derived HMGB1 is speculated to exert a regulatory effect on MDSCs, but no report has confirmed this hypothesis. Therefore, the effects of HMGB1 on MDSCs need more research attention, and additional investigations should be conducted.